2016
DOI: 10.18632/oncotarget.8153
|View full text |Cite
|
Sign up to set email alerts
|

The altered glucose metabolism in tumor and a tumor acidic microenvironment associated with extracellular matrix metalloproteinase inducer and monocarboxylate transporters

Abstract: Extracellular matrix metalloproteinase inducer, also knowns as cluster of differentiation 147 (CD147) or basigin, is a widely distributed cell surface glycoprotein that is involved in numerous physiological and pathological functions, especially in tumor invasion and metastasis. Monocarboxylate transporters (MCTs) catalyze the proton-linked transport of monocarboxylates such as L-lactate across the plasma membrane to preserve the intracellular pH and maintain cell homeostasis. As a chaperone to some MCT isofor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 152 publications
1
31
0
Order By: Relevance
“…While predominantly recognized for its role in multiple biological processes, such as immune response, tumour progression, matrix proteolysis and cell migration, it has also been shown to be involved especially in neovasculogenesis under hypoxia during tumour invasion and metastasis 10. Especially, it has been reported that basigin may promote angiogenic process not only through its protease‐inducing function by up‐regulating matrix metalloproteinase (MMPs) secretion 11, 12, but also directly by its ability to increase soluble forms of VEGF and VEGFR2 in tumour cells and endothelial cells 13, 14, 15.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While predominantly recognized for its role in multiple biological processes, such as immune response, tumour progression, matrix proteolysis and cell migration, it has also been shown to be involved especially in neovasculogenesis under hypoxia during tumour invasion and metastasis 10. Especially, it has been reported that basigin may promote angiogenic process not only through its protease‐inducing function by up‐regulating matrix metalloproteinase (MMPs) secretion 11, 12, but also directly by its ability to increase soluble forms of VEGF and VEGFR2 in tumour cells and endothelial cells 13, 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…tumour invasion and metastasis [10]. Especially, it has been reported that basigin may promote angiogenic process not only through its protease-inducing function by up-regulating matrix metalloproteinase (MMPs) secretion [11,12], but also directly by its ability to increase soluble forms of VEGF and VEGFR2 in tumour cells and endothelial cells [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of human tumors exhibit significantly higher glucose flux than adjacent normal tissues . Moreover, glucose metabolism in tumors is characterized by increased aerobic glycolysis, even in the presence of sufficient oxygen . The crucial roles of numerous oncogenic signals mediated by some well‐known oncoproteins and tumor suppressor proteins in metabolic reprogramming have been revealed, including the PI3K/Akt/mTOR, Myc, and hypoxia‐inducible factor pathways, which mediate increases in glucose uptake and glycolysis.…”
Section: Discussionmentioning
confidence: 99%
“…42 Moreover, glucose metabolism in tumors is characterized by increased aerobic glycolysis, even in the presence of sufficient oxygen. 43 The crucial roles of numerous oncogenic signals mediated by some well-known oncoproteins and tumor suppressor proteins in metabolic reprogramming have been revealed, 44,45 including the PI3K/Akt/mTOR, 46,47 Myc, 48 60 and irreversible small-molecule inhibitors ( 18 F-afatinib) 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these data suggested that CD147 was able to mediate drug resistance in breast cancer cells though interacting with V-ATPase. CD147 has also been demonstrated to specifically be associated with cell surface expression and the appropriate location of MCTs as a chaperone in the energy metabolism of tumors, thus contributing to the tumor invasion, metastasis and drug resistance (24,(47)(48)(49). In addition, CD147 have been observed to influence tumor drug resistance through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%